# An equation is shown below:. . -2(4x - 1) - 7 = 5. . Which statement shows a correct next step in solving the equation? . . The equation can become -2(4x - 1) = -2 by applying the distributive property.. The equation can become -2(4x - 1) = 12 by applying the addition property of equality.. The equation can become -2(4x - 1) = 12 by applying the commutative property of addition. The equation can become -2(4x - 1) = -2 by applying the subtraction property of equality.

(1) Answers

Add answer

Sign in
Sign up